Organizational Processes and Strategic Positioning in Telecommunication Industry in Kenya - Kinyua, Jesse; M'Kuma, Ezekiah; Kariuki, Samuel (Research Gate, 2019)
The steady growth on mobile and internet connectivity has increased growth in telecommunication industry. The changed environment has necessitated a new business model in the telecommunication industry structure aiming at building resource capabilities and strategic positioning in the fast changing business environment. The study established how organization processes led to strategic positioning in telecommunication industry. The study was carried out from the entire mobile and network operators licensed by Communication Authority of Kenya. These were Safaricom limited, Airtel Kenya, Orange Kenya and Equitel Kenya. Descriptive statistics as mean scores, standard de viation were used in this study. The study used Pearson Correlation to measure strength of linear relationship between variables. The research adopted multiple regression analysis in testing of variables. A Census method was used on strategic planning mana gers and C.E.O’s from 188 customer care centers from the four mobile and network operators. Primary data were collected using semi-structured questionnaires. The questionnaires were administered to all Strategic planning Managers at customer care centers at headquarter offices for four companies in 47 counties. The study found that organization processes in telecommunication industry significantly affected strategic positioning. The study established that there was a strong statistically significant. The study recommends that telecommunication industry should invest in improvement of organization processes through innovation in order to position itself strategically in a vast changing environment.
Keywords: Organizational processes; strategic positioning; telecommunication industry